High Prevalence and Genetic Diversity of Human Norovirus Among Children Under 5 Years Old with Acute Gastroenteritis at the Dr. Leonardo Guzmán Regional Hospital, Antofagasta, Chile, 2019 - Andrea M. Avellaneda; Claudia P. Campillay-Véliz; Daniela C. Reyes; Daniel Herrera; Christian A. Muñoz; Jan Vinjé; Margarita K. Lay (Viruses)
Acute gastroenteritis (AGE) has one of the highest rates of morbidity and mortality among children under five years old worldwide. It is estimated that 1.7 billion cases of childhood diarrheal diseases occur annually, leading to up to 443,832 deaths. Approximately 90% of these cases are viral, with human norovirus being the main cause in countries that have implemented rotavirus vaccines. The objective of this study was to describe the prevalence and genetic diversity of norovirus in child outpatients and inpatients under five years old at the Regional Hospital of Antofagasta. From 1 January to 31 October 2019, a total of 121 stool samples were collected to detect the presence of norovirus GI and GII using Taqman™-based real-time RT-PCR. Norovirus RNA was detected in 50 (41.3%) samples, of which 96% were typed as GII.4 Sydney (42% GII.4 Sydney[P16] and 54% GII.4 Sydney[P4 New Orleans]). Furthermore, most (92%) of the positive specimens were from children under two years of age and a majority were detected in April (38%) and May (20%). Our findings highlight the high burden of norovirus in hospitalized children with AGE and the importance of molecular strain surveillance to support vaccine development.